Hydrogel-based asymmetrical membranes for wound dressing application: manufacture, drug delivery and wound-healing effects - Ferreira, Patrícia Isabel da Cruz Morgado (2018)
The development of new wound dressings able to mimic the native structure of skin and to allow a faster and less-painful healing process is an urgent demand. Dry, clean and ready-to-use poly(vinyl alcohol)/chitosan (PVA/CS) asymmetrical dressings were successfully developed through supercritical carbon dioxide (scCO2)-phase inversion technique in just 4h instead of the 24h required when conventional methods, wet- and dry/wet-phase inversion, are used. The produced dressings were recovered in a dry state, but they can form a hydrogel due to their high water uptake ability, which is an important property for maintaining a moisturized environment for improving the wound healing process. They presented a dense skin top layer of about 15 μm, that allows gaseous exchange while avoiding microorganisms penetration, and a porous inner layer able to remove the excess of exudates. To evaluate the suitability of these membranes for use as drug delivery systems, ibuprofen (IBP) was loaded in these membranes as drug model. However, due to the hydrogel-like properties, the IBP loaded into PVA/CS dressings was completely released after 40 minutes, which is not appropriate for wound healing purposes. To overcome such drawback, IBP-β-cyclodextrins (β-CDs) complexes and IBP-loaded poly(1,3-glycerol dimethacrylate) microbeads were used to customize the release profile of IBP and to allow the application of the dressings in the treatment of full-thickness wounds. The results obtained reveal that β-CDs allowed a sustained drug release during 3 days, which is compatible with the time frame of the inflammatory phase. Moreover, the data collected from in vivo assays showed that the presence of a simple anti-inflammatory and pain-relief drug within dressings was crucial to avoid an acute inflammatory phase and scab formation, thus promoting a faster skin renewal.